Physiocognitive Modeling: Explaining the Effects of Caffeine on Fatigue. (30th May 2022) - Halverson, Tim; Myers, Christopher W.; Gearhart, Jeffery M.; Linakis, Matthew W.; Gunzelmann, Glenn
Abstract: Most computational theories of cognition lack a representation of physiology. Understanding the cognitive effects of compounds present in the environment is important for explaining and predicting changes in cognition and behavior given exposure to toxins, pharmaceuticals, or the deprivation of critical compounds like oxygen. This research integrates physiologically based pharmacokinetic (PBPK) model predictions of caffeine concentrations in blood and tissues with ACT‐R's fatigue module to predict the effects of caffeine on fatigue. Mapping between the PBPK model parameters and ACT‐R model parameters is informed by the neurophysiological literature and established associations between ACT‐R modules and brain regions. The results from three such parameter mappings are explored to explain observed data from sleep‐deprived participants performing the psychomotor vigilance test with and without caffeine. Predicted caffeine concentrations in the brain are used to modulate procedural parameters in the fatigue module to explain caffeine's effects on multiple performance metrics. Abstract : Understanding the effects of environmental compounds on cognition is important for predicting changes in performance. This research integrates physiologically‐based pharmacokinetic (PBPK) model predictions of caffeine with ACT‐R's fatigue module to predict the effects of caffeine and fatigue on the psychomotor vigilance task.